Analisis Hukum Internasional Terhadap Allowable Catch Dalam Upaya Pencegahan Praktik Overfishing Dan Penerapannya Di Indonesia - Zunit, Jemie Devano; Zora, Zimtya (Nagari Law Review, 2024)
The sea has a tremendous amount of potential, with an abundance of fish and very astounding biodiversity. However, nowadays, many irresponsible individuals overexploit the biological riches in the sea, resulting in overfishing. Overfishing is a method of excessive fishing that will cause a drastic and continuous decline in fish populations, which will later lead to extinction. For this reason, we need a way to suppress overfishing, namely implementing allowable catch. Coastal states can use allowable catch as a management technique to limit fishing in certain areas. This study used normative juridical research methods with descriptive research specifications and analyzed them through library research. Under international law on Article 61 of UNCLOS 1982, the allowable catch has been regulated to reduce overfishing rates. To determine the allowable catch, use the formula JTB = 80% x MSY. The implementation of allowable catch in Indonesia has been regulated in the Ministerial Decree of Maritime Affairs and Fisheries Republic of Indonesia Number 19 of 2022 concerning the Estimation of Fish Resource Potential, JTB, and the Level of Fish Resource Utilization in the Fisheries Management Areas of the Republic of Indonesia.